Amount and seasonal trend of gains of yearling steers on bluestem pasture - Pickett, A.G.; Smith, E.F. (Kansas Agricultural Experiment Station, 2012)
One hundred thirty-five yearling steers which had been wintered as calves at Guymon, Oklahoma, on short grass, sorghum bundles, prairie hay and cottonseed cake, were, furnished to Kansas State College by the Robbins Ranch of Belvidere, Kansas. These steers were thin in flesh but were thrifty in condition. Beginning weights were taken after the steers had been at the college about one week. They were fed hay and a small feed of silage and weighed with a normal fill. No protein or other supplement was fed.
Keywords: Beef; Gain; Bluestem pasture; Yearling steers